UPAYA PENANGGULANGAN KEKERASAN ANAK DI SURABAYA MELALUI KEMITRAAN PEMERINTAH SURABAYA DENGAN UNICEF (2021-2023) - Sindi Fellicia Puguh Hermanto; Renitha Dwi Hapsari (Halu Oleo University, 2024)
This research aims to provide an explanation of efforts to overcome violence against children in Surabaya in the period 2021 to 2023 which are implemented through partnerships with the UNICEF. This research uses the concept of violence and protection against children and is based on Finnemore & Sikkink's norm life cycle theory in providing an overview of the norm internalization process by the Surabaya City Government as an effort to create a Child Friendly City in the world. The author also uses Ali Khamdan's international partnership theory regarding partnership steps. To carry out qualitative data analysis, this research uses interviews, observation and document analysis method. Based on the research results, the implementation of the Surabaya City Government partnership in overcoming child violence in Surabaya was carried out through 8 stages of Ali Khamdan's partnership theory starting from problem recognition to the monitoring stage. After signing the memorandum of understanding, this partnership is still being implemented. Several actions have been taken, such as correspondence to Bappenas and UNICEF by the Surabaya City Government, UNICEF visited Surabaya, there were work program preparation meetings, and monitoring supervised by Bappeda.